Rules: Society, Language, Rationality - Koreň, Ladislav (Teorie vědy / Theory of Science, 2012)
This critical review focuses on the topic of cooperation and rules discussed in the book by Jaroslav Peregrin: Človek a pravidla [Man and Rules] (Praha: Dokořán 2011). Except of an extensive excurse into the structure of Peregrin’s main ideas and arguments, it aims to provide a systematic analysis of some central issues in this interdisciplinary theoretical field, while discussing some elements of Peregrin’s specific approach. In particular, it will be argued that Peregrin’s preferred conception of rule - as propositional knowledge to the effect that something ought to be (or ought not to be) a certain way - cannot serve well his purposes, if Peregrin is to keep his evolutionary perspective on rules.